118 Innovating Pediatric Behavioural Assessments and Care Pathways: Community Consultation Phase. (19th August 2020) - Gander, Sarah; Campbell, Sarah; Flood, Kate; Robinson, Bryn
Abstract: Background: It is well-documented that children facing social disparities, trauma and toxic stress will experience a disproportionate number of negative physical and mental health outcomes across their lifespan. A common manifestation of this is the increasing prevalence of behaviour-related diagnoses in school-aged children. Regardless of whether a child suffers from a true behaviour disorder, or if they are displaying symptoms that relate to complex and challenging social conditions, they require a thoughtful, collaborative and inclusive approach to their care. Community Social Pediatrics adopts such an approach. Objectives: The objective of the current study is to examine and understand the experiences of children and their families during the referral and treatment process for pediatric behavioural referrals in our local region. We will also explore the perspective of service providers on the challenges and strengths of the current system. Design/Methods: A focus group (n=8) using semi-structured group interviews was conducted with caregivers whose children were in various stages of care/treatment regarding behavorial issues in the region surrounding Saint John, NB. Questions focused on: experiences in the system; efficacy of services; the child's experience; wait times; and system cohesion. Qualitative thematic analysis was used to analyze the data. Through a strategic planning exercise (n=26), we were able to engage service providers and experts in this area to delineate the challenges and strengths that they perceive in the current system, and to provide insights they have into working with families. Results: The major themes identified by families were defined by positive interactions, negative interactions, barriers, their own behavioural responses to the system and the impact on the child. Families' positive experiences were associated with respectful and effective communication, integrated wrap-around services, assistance with navigation, and a child-centred approach. Negative experiences were rooted in feeling stigmatized by service providers, lack of communication between service providers, and inadequate mental health services for children. A number of system and personal barriers were identified. The service providers echoed these issues: provide equitable and efficient access to services; understand the needs of the family; strengthen relationships with partners and clients; and create a supportive working environment. Conclusion: Consultation with families and service providers identified a number of issues in how children access and engage with community services. Community Social Pediatrics seeks to impact health at the community level and addresses the needs of children in a way that reflects the social context of their lives, community and society. Assessment and care procedures that are delivered through this model aim to remove barriers, reduce fragmentation and increase collaboration and communication across the entire care team.